2002
DOI: 10.1179/026708302225005945
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of scratch damage in polypropylene

Abstract: Atomic force microscopy (AFM) in tapping mode has been used to characterise surface damage on deformed polypropylenes induced during a scratch test. Atomic force micrographs revealed differences in microstructures that could be used to predict the deformation resistance of two different types of polypropylene. The undeformed surface of the two types of polypropylene (identi® ed as polypropylene-L and polypropylene-R) was characterised by differences in arrangement (regular or irregular) of ® brils depending on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…Strain rate has a complicated and dramatic effect on materials deformation processes because the energy expended during plastic deformation is largely dissipated as heat. This process was observed to be more prominent at higher loading rates that are associated with adiabatic drawing than during lower loading rates where isothermal drawing occurred [10,11].…”
Section: Introductionmentioning
confidence: 86%
“…Strain rate has a complicated and dramatic effect on materials deformation processes because the energy expended during plastic deformation is largely dissipated as heat. This process was observed to be more prominent at higher loading rates that are associated with adiabatic drawing than during lower loading rates where isothermal drawing occurred [10,11].…”
Section: Introductionmentioning
confidence: 86%
“…Even though the region appears to be brittle, there are a large number of unbroken fibrils that continued to plastically deform as decohesion of fibrils progressed. It is also relevant to note here that atomic force microscopy of the brittle region indicated that it involves reorganization of microstructure signifying reduced stretching of fibrils resulting in an irregular surface morphology at the micrometric scale [26].…”
Section: Neat High Crystallinity Polypropylenementioning
confidence: 99%
“…Misra and co-workers [23,24] believe that polymeric materials characterized by high modulus and yield strength, and a large elastic regime are preferred materials in applications where mechanically induced surface damage is the primary concern. Mechanically induced surface damage in the form of scratch or internal damage in the form of voids undermines the longevity of the polymeric components and limits their use [25,26]. The minimization of plastic deformation (or stress whitening) can be accomplished by increasing crystallinity [27], use of short chain polymers [28], compounding with additives, and a significant influence can be realized by reinforcement of polymers with micrometric size particles, such as wollastonite and talc minerals.…”
Section: Introductionmentioning
confidence: 98%
“…This effect was observed to be more prominent at high crosshead speeds associated with adiabatic drawing rather than during small crosshead speeds where isothermal drawing occurs. 26,28 Termonia et al 29 reported that each molecular weight exhibits a different temperature or elongation window within which optimum drawing occurs. Within these windows, the rate of slippage of chains through entanglements reaches its optimum value.…”
Section: Introductionmentioning
confidence: 98%